Terpaan Iklan Digital, Word Of Mouth dan Komunikasi Pemasaran Interaktif pada Keputusan Pembelian Produk Perawatan Tubuh: Terpaan Iklan Digital, Word Of Mouth dan Komunikasi Pemasaran Interaktif pada Keputusan Pembelian Produk Perawatan Tubuh - Paramita Purnama; Rosita Anggraini; Arintowati Hartono; Irwansyah; Niken F. Ernungtyas (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Media Social Instagram turn marketing communication into interactive. On the other hand conventional approaches such as word of mouth are still used to drive purchasing decisions. The study discusses four main concepts namely exposure to advertising on social media, word of mouth, and interactive marketing communication as independent variables. While the purchase decision as the dependent variable. The article aims to describe the influence between advertising exposure, word of mouth and interactive marketing communication on purchasing decisions in the context of body care products and services. This study collects data through online surveys. Respondents (n = 100) come from Instagram account followers @thecliniccipete and are chosen based on membership or have made a previous purchase. Data analysis used univariate analysis for demographic data and bivariate analysis for variables. Bivariate analysis uses simple linear regression to test three hypotheses. The result of regression test shows that statistically all hypotheses have an influence on purchasing decisions with different levels of influence strength. Ad exposure and word of mouth variables show a strong influence on purchasing decisions. However, interactive marketing communication shows a moderate influence on purchasing decisions. Based on the three hypotheses known word of mouth is the most powerful variable that explains purchasing decisions in the context of body care products and services.